Modified LDL Immune Complexes and Cardiovascular Disease - Lopes-Virella, Maria F.; Virella, Gabriel (Current Medicinal Chemistry, 2019)
Modified forms of LDL, both spontaneously formed in the organism or prepared in the laboratory, are immunogenic. As a consequence, antigen-antibody complexes (immune complexes, IC) formed in vivo can be measured in the peripheral blood, and their levels are strong predictors of cardiovascular disease (CVD). It has been possible to generate antibodies that recognize different LDL modifications, allowing the analysis of circulating IC constitution. Clinical studies showed that the antigenic constitution of the IC has a modulating effect on the development of CVD. Patients whose IC react strongly with antibodies to copper oxidized LDL (oxLDL) show progressive development of atherosclerosis as demonstrated by increased intima–media thickness and increased coronary calcification scores. In contrast, patients whose IC react strongly with antibodies to the heavily oxidized malondialdehyde LDL prepared in vitro (MDA-LDL) are at a high risk of acute vascular events, mainly myocardial infarction. In vitro studies have shown that while oxLDL IC induce both cell proliferation and mild to moderate macrophage apoptosis, MDA-LDL IC induce a more marked macrophage apoptosis but not cell proliferation. In addition, MDA-LDL IC induce the release of higher levels of matrix metalloproteinases and TNF than oxLDL IC. High levels of TNF are likely to be a major factor leading to apoptosis and high levels of metalloproteinases are likely to play a role in the thinning of the fibrous cap of the atheromatous plaque. The combination of apoptosis and fibrous cap thinning is a well-known characteristic of vulnerable plaques, which are more prone to rupture and responsible for the majority of acute cardiovascular events.
Keywords: MDA-LDL